Interdisciplinary relations in teaching computer technologies in gymnasium - Kaklauskas, Liudvikas; Kaklauskienė, Danutė (Lietuvos matematikos rinkinys, 2002)
In the article discuss about teaching of computers technology in the secondary school. Analysis relationships between this thing and others disciplines which is teaching. Look for best methods to use in investigation of this course.